2014
DOI: 10.1007/s11596-014-1344-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholic acid on fetal cardiac myocytes in intrahepatic choliestasis of pregnancy

Abstract: This study examined the effect of cholic acid (CA) on cultured cardiac myocytes (CMs) from neonatal rats with an attempt to explore the possible mechanism of sudden fetal death in intrahepatic cholestasis of pregnancy (ICP). Inverted microscopy was performed to detect the impact of CA on the beating rates of rat CMs. MTT method was used to study the effect of CA on the viability of CMs. CMs cultured in vitro were incubated with 10 μmol/L Ca(2+)-sensitive fluorescence indicator fluo-3/AM. The fluorescence signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Chenodeoxycholic acid was able to activate the NLRP3 inflammasome in macrophages, which could primarily induce interleukin 1β and aggravates the inflammatory process and affects epithelial integrity by inducing the production of pro-inflammatory cytokines [47]. Cholic acid may influence cardiac electrophysiology, inhibiting the activity of cardiac myocytes, causing calcium overload, and leading to sudden fetal death, and hence might influence cardiac electrophysiology [48]. Furthermore, it has been reported that cholic acid could strongly reduce endoplasmic reticulum stress by inhibiting extracellular signal−regulated kinase signaling and endoplasmic reticulum stress−related activating transcription factor 4 [49].…”
Section: Resultsmentioning
confidence: 99%
“…Chenodeoxycholic acid was able to activate the NLRP3 inflammasome in macrophages, which could primarily induce interleukin 1β and aggravates the inflammatory process and affects epithelial integrity by inducing the production of pro-inflammatory cytokines [47]. Cholic acid may influence cardiac electrophysiology, inhibiting the activity of cardiac myocytes, causing calcium overload, and leading to sudden fetal death, and hence might influence cardiac electrophysiology [48]. Furthermore, it has been reported that cholic acid could strongly reduce endoplasmic reticulum stress by inhibiting extracellular signal−regulated kinase signaling and endoplasmic reticulum stress−related activating transcription factor 4 [49].…”
Section: Resultsmentioning
confidence: 99%
“…Only one ex vivo study examined the effects of CA on contraction and viability in primary neonatal rat cardiomyocytes ( Gao et al, 2014 ). In this study, CA decreased the contraction rates and reduced the viability of neonatal rat cardiomyocytes through an increase in concentration of intracellular Ca 2+ ( Gao et al, 2014 ).…”
Section: Effects Of Bile Acids On Cardiomyocytes ( Table 1 ...mentioning
confidence: 99%